Eosinophilic angiitis presenting with a true, fusiform, temporal artery aneurysm. Issue 6 (8th April 2017) - MacDiarmid, Megan; Nepogodiev, Dmitri; Tiwari, Alok; Duddy, Martin; Carey, Martyn; Jobanputra, Paresh
Key Clinical Message: Temporal artery aneurysm is a rare cause of temporal artery swelling in the absence of preceding trauma. Vasculitis other than giant cell arteritis, such as eosinophilic granulomatosis with polyangiitis, should be considered in such cases and a careful assessment of other medium‐sized arteries undertaken. Abstract : Temporal artery aneurysm is a rare cause of temporal artery swelling in the absence of preceding trauma. Vasculitis other than giant cell arteritis, such as eosinophilic granulomatosis with polyangiitis, should be considered in such cases and a careful assessment of other medium‐sized arteries undertaken.